Collection of Different Ayurvedic Formulations Used In Polycystic Ovarian Syndrome - choudhary, Susheela (International Research Journal of Ayurveda & Yoga, 2021)
The PCOS is one of the most frequent endocrine disease in women of reproductive age with a prevalence of 9.13% in Indian population. It is characterized by hyper-androgenism and chronic anovulation. As PCOS is associated with hyperinsulinemia it has major metabolic as well as reproductive morbidities. Promisingly lifestyle intervention comprising dietary, exercise and behavioural therapy improve fertility and reduce cost per birth significantly. PCOS is an upcoming problem in gynaecology OPD. The first step done in general practice in OPD’s when a patient of PCOS comes is to advise weight reduction. Weight reduction in obese patient is the initial recommendation because it reduces insulin, SHBG and androgen levels and may restore ovulation. The treatment modalities aim at providing comprehensive care by correcting the ama dosha (insulin levels), achieving Koshta Shuddhi and regulating Tridoshas, by this the menstruation is regularized and fertility is restored. According to Ayurveda PCOS is a disorder involving Pitta, Kapha & Vata Doshas. Rasa & Meda Dhatu, Rasa, Rakta & Artava Vaha Strotasa. The properties of deepana (appetizer) & pachana (digestive) of below discussed drugs they elevate the Jatharagni, Dhatwagni as well as Artavagni. Use of Agneya Dravya remove Avarana of Artava and maintain flow of Artava (menstrual blood). There is also kapha reducing, insulin enhancing & hormone rebalancing, drugs help to relieve the symptoms PCOS.